1992
DOI: 10.1021/jm00094a005
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antiviral activity of methyl derivatives of 9-[2-(phosphonomethoxy)ethyl]guanine

Abstract: A number of methyl derivatives of 9-[2-(phosphonomethoxy)ethyl]guanine (PMEG, 1) have been synthesized and tested in vitro for anti-herpes and anti-human immunodeficiency virus (HIV) activity. Among these analogues, (R)-2'-methyl-PMEG [(R)-3] and 2',2'-dimethyl-PMEG (7) demonstrated potent anti-HIV activity in the XTT assay with EC50 values of 1.0 and 2.6 microM, respectively. The corresponding (S)-2'-methyl-PMEG [(S)-3] was found to be less potent against HIV. In addition, the (R) and (S) enantiomers of 9-[3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…The mixture of bromophosphonates (compounds 5 and 6) was readily separable by flash chromatography (10 to 20% acetone in hexanes), and the relative stereochemistry was assigned by a Nuclear Overhauser Effect experiment with the corresponding bromophosphonic acids. Condensation of the bromide (compound 6) with 2-amino-6-chloropurine in the presence of Cs 2 CO 3 (50) in dimethylformamide at 95°C gave 6-chloropurine (compound 7) in a 42% yield. The phosphonate ester was deprotected by treatment with excess bromotrimethylsilane, followed by concomitant hydrolysis of the resulting trimethylsilyl ester and the 6-chloropurine to the guanine compound (compound 1) by refluxing in water; the phosphonic acid was sufficiently acidic to smoothly effect the last transformation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mixture of bromophosphonates (compounds 5 and 6) was readily separable by flash chromatography (10 to 20% acetone in hexanes), and the relative stereochemistry was assigned by a Nuclear Overhauser Effect experiment with the corresponding bromophosphonic acids. Condensation of the bromide (compound 6) with 2-amino-6-chloropurine in the presence of Cs 2 CO 3 (50) in dimethylformamide at 95°C gave 6-chloropurine (compound 7) in a 42% yield. The phosphonate ester was deprotected by treatment with excess bromotrimethylsilane, followed by concomitant hydrolysis of the resulting trimethylsilyl ester and the 6-chloropurine to the guanine compound (compound 1) by refluxing in water; the phosphonic acid was sufficiently acidic to smoothly effect the last transformation.…”
Section: Methodsmentioning
confidence: 99%
“…Thereafter, infected-treated cells were subjected to one freeze-thaw cycle and then the virus titer in the cell lysates was determined as described in Materials and Methods. 50 was defined as the concentration of compound that resulted in a 50% reduction in plaque number compared to the number observed in control samples without drug. IC 50 s were calculated from dose-response curves obtained after linearly regressing the percent reduction of plaques against drug concentrations.…”
mentioning
confidence: 99%
“…This effort could result in a new lead, or even a drug candidate. (R)-2 -methyl-PMEG looked very promising in that the selectivity was improved in cells [20]. However, animal studies still showed unacceptable toxicities.…”
Section: Antiviral Nucleotide Analoguesmentioning
confidence: 99%
“…For the synthesis of other target ANPs, compounds 5 – 9 ( Scheme 2 ), previously reported 26 , 30 34 guanine containing ANPs 11 – 15 , have been exploited as a starting material. Standard diazotization of compounds 11 – 15 followed by 2-hydroxy-dediazoniation afforded the desired xanthine-based ANPs 5 – 9 in moderate to good yields (36–82%).…”
Section: Chemistrymentioning
confidence: 99%